The Quality of Work Life for Faculty Members at Jordan University of Science and Technology - Hammam Samir Hamadne (University of Science and Technology, Yemen, 2019)
This study aimed at identifying the quality of work life for faculty members at Jordan University of Science and Technology from their perspective. To achieve the objective of the study, a questionnaire was developed, which consisted of (35) items and was divided into six dimensions: leadership style, stability and job security, career promotion, salaries and remuneration, the balance between university work and social life, professional development (training and education).The questionnaire was distributed to the sample of the study, which consisted of (420) faculty members during the first semester (2018/2019). After conducting the statistical analysis of the data, the major results of the study were as follows: The quality of work life of the faculty members at Jordan University of Science and Technology was very high for all dimensions and the questionnaire as a whole. There were statistically significant differences due to the gender variable for all the dimensions of study and the tool as a whole in favor of (females) except for the dimensions of stability and job security and balance between university work and social life. There were also statistically significant differences due to the academic rank for all dimensions of the study and the tool as a whole in favor of (the associate professor, and assistant professor). The study recommended further studies on the subject of quality of work life of the faculty members in other Jordanian universities with other independent variables.